Through "Poverty's Vale" : A Hardscrabble Boyhood in Upstate New York, 1832-1862 - Conklin, Henry, 1832-1915 (York State book., 2021)
Conklin's personal writings illuminate his pioneer youth and struggles in upstate New York and service in the Civil War